The Role of Leadership in Teacher Performance in Public Schools - Pitdianti, Nova; Endini, Maulida Isnaini; Nurhalizah, Siti; Elfrianto, Elfrianto (EDUCTUM: Journal Research, 2024)
Leadership in managing responsibility has a significant effect on achieving success and is a determining factor in improving or decreasing the quality of performance led. An ideal leader is able to have a positive impact on performance. Teachers, as part of the educational staff, play a very important role in the formation of human resources in the world of education. The quality of school education is greatly influenced by the competence of teachers in carrying out their duties. Improving the quality of teachers is very important because of the weaknesses in the teacher's soul itself. Teacher performance is the result of implementing a plan that has been prepared based on the teacher's skills, experience, sincerity, competence, motivation, and responsibility in achieving goals. This includes the tasks of educating, teaching, guiding, directing, training, and evaluating students to achieve the quality and quality of learning. The focus of this literature review is on the role of principal leadership in improving teacher performance in schools, based on published articles. This study uses a literature review methodology as part of its research investigation. The analysis method collects information about decision making and the role of leaders from books and journals to conduct a literature study. There are various resources available for literature studies, such as books, journals, notes, the internet, and libraries. This study discusses the role of principal leadership on teacher performance in public schools. The research data was taken from various sources, including books, journals, and previous research. This study uses qualitative methods.